O olhar do professor e dos alunos do ensino médio sobre o currículo de educação física do estado de São Paulo - Bonato, Neusa Aparecida Mendes [UNESP] (2014)
Education policies for Basic Education in Brazil, since the LDBEN # 9394/96 promulgation, have brought along significant changes, like the extension of obligatory attendance to all schooling stages, the implementation of school and students assessment systems, as well as guidelines and curriculum documents that propose a national common ground. In order to develop this study, we have addressed theoretical approaches to the curriculum field and the educational policies that form the curricular bases for Secondary School. In addition, we have situated Physical Education historically, as well as its connections to the school institution. In line with such changes, Secondary School has gained prominence in recent years, with offer and obligation extension, besides the search for a new identity, aiming at improving the quality of teaching. The research's aim was to analyse the Secondary School Physical Education Curriculum in São Paulo State, implemented in 2010, verifying all its practical implications in three grades at a state school in the city of Araraquara (SP), according to the teachers' and the students' view over the Curriculum and the didactic material: the Teacher and Student Notebooks. The participants were: one Physical Education teacher and 84 Secondary School students. Results suggest that Secondary School represents a phase of preparing for entering higher education and labour market for most of the participating students. There was a demand for other contents/themes besides sports. Many students pointed out ENEM in their answers and the knowledge presented in the Curriculum can help them with that test. They gave critical opinions about multiple aspects related to the lessons, such as the Physical Education Curriculum, material conservation and material absence. In the teacher's opinion, the activity that started in 2008 with the Students Journal (Jornal do Aluno) has brought up obstacles among students and their parents ...